Pseudomyxoma Peritonei in a Case of Carcinoma Cervix: Subtle Finding With Implications on Management and Prognosis - Sarita Kumari; Suvidya Singh (Case Reports in Oncological Medicine)
Pseudomyxoma peritonei (PMP) is a well-known entity in gastrointestinal and ovarian tumors of mucinous histology. It has important implications on prognosis depending on whether seen in conjunction with a benign or a malignant tumor. In the current report, we describe a case of PMP in a case of advanced endocervical adenocarcinoma of the cervix which was managed surgically.